2021
DOI: 10.4102/sajip.v47i0.1832
|View full text |Cite
|
Sign up to set email alerts
|

Relating job satisfaction and organisational commitment: The moderating and mediating roles of positive individual strengths

Abstract: Orientation: This rapidly changing world requires local government institutions to focus on positive work-related states to enhance quality service delivery.Research purpose: The main objective of this article was to explore how individual traits and psychological strengths (i.e. adult state hope, meaning in life and work locus of control) moderate or mediate the relationship between job satisfaction and organisational commitment in a Botswana local government institution.Motivation for the study: The emergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The other factors were interpreted in the same manner. All Cronbach's alphas were above the threshold of 0.6, as suggested byMaree (2016)…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…The other factors were interpreted in the same manner. All Cronbach's alphas were above the threshold of 0.6, as suggested byMaree (2016)…”
mentioning
confidence: 56%
“…Setiadi and Warmika (2015) opine that positive emotions are conditions in which a person experiences feelings of pleasure or joy. Hence, emotionally stable employees tend to support the municipality's strategic objectives (Masale et al, 2021). Researchers have shown that municipal managers who support and allow employees to participate in municipal strategic decision-making, such employees display happiness and a high level of job satisfaction (Purnomo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This can either encourage their involvement in organisational activities or decrease their involvement (Saks, 2006, p. 601). Employees who feel less committed to the organisation will feel less satisfied with their work, affecting their engagement, performance and productivity (Ariani, 2013;Chanana & Sangeeta, 2020;Masale et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For Ababneh et al (2021) productivity and efficiency can benefit from employee commitment. Also, Masale et al (2021) mention that a high degree of organizational commitment reduces aspects such as absenteeism and staff turnover in the company, for example.…”
Section: Introductionmentioning
confidence: 99%